Segmentasi Politik Pemilih Pasangan Pemenang Pemilu Kepala Daerah dan Wakil Kepala Daerah Kota Padang Tahun 2008 - Eka Putri, Nora (Fakultas Ilmu Sosial Universitas Negeri Padang, 2011)
ABSTRACT On the slope of Local Government Election of Padang in 2008 there were five pairs of mayor and deputy mayor candidates, among other candidates was Fauzi Bahar and Mahyeldi (Coalition PAN and PKS) that gets the most votes in the election of regional head and deputy regional head of Padang. Efforts were made ​​could not be separated from political parties or candidates foresight in carrying the work program as well as segmentation of the electorate. The study examines the political segmentation of the voters for election winner slope of Padang Local Government on the aspects of policy-oriented problem-solving and ideological orientation. The finding of this study indicated that policy-oriented problem-solving that involved mass media in electoral politics segmentation of Fauzi Bahar-Mahyeldi voters is not too significant. Furthermore, economic performance and political responsibilities were more emphasized on the process of imaging and